An Assessment Case Report of Special Child with Behavioral and Learning Disorders - Syeda Eisha Bukhari; Nida Mushtaq (Research Journal of Psychology, 2025)
A child R.H is 12 years old boy, who was brought by his father to slow learner’s institute Muzaffargarh for admission and assessment. He was drop out from general education school. The reason for refer to special education school due to his hyperactive and disturbing behavior. Complaints regarding class fellows (physical and verbal fights abusive language) Lack of interest in studies, carelessness in hygiene and concentration problems. Which was diagnosed later un-specified Attention –Deficit/Hyperactivity Disorder. The psychologist used clinical interview with mini mental stat examination. Behavioral observation, Ravens colored progressive metrics (CPM) for diagnosis. Slossons’s intelligence test was administered to determine the I.Q of the child with curriculum base short assessment test with slow learner screening tool was administered to measure child intellectual level .Screening tool result was moderate to severe in cognitive, academic domains results also shows disturbance in social and emotional domains. Therapeutic techniques include structured targeted individual sessions, rapport building, planned ignoring (dramatic behavior), positive reinforcement, functional communication training were used to work on presenting complaints behavior. Differential instructions method and targeted curriculum modification was done for improvements in educational learning difficulties. Post assessment done on the end of the therapy and interventions. Results shows significant improvements in behavior as reported by the parents’. A significant and gradually improvement shows in his educational results.